2012
DOI: 10.1186/1744-8069-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperalgesic Effects of Calcitonin on Neuropathic Pain Interacting with its Peripheral Receptors

Abstract: BackgroundThe polypeptide hormone calcitonin is clinically well known for its ability to relieve neuropathic pain such as spinal canal stenosis, diabetic neuropathy and complex regional pain syndrome. Mechanisms for its analgesic effect, however, remain unclear. Here we investigated the mechanism of anti-hyperalgesic action of calcitonin in a neuropathic pain model in rats.ResultsSubcutaneous injection of elcatonin, a synthetic derivative of eel calcitonin, relieved hyperalgesia induced by chronic constriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…It was previously demonstrated in many prospective studies that subcutaneous or intranasal application of SC exhibited analgesic effects . It was shown that calcitonin provided anti‐hyperalgesic effect on pain behaviours in chronic constriction injury‐induced hyperalgaesia in rats . In a clinical prospective study, 200 IU of intranasal SC was administered to postmenopausal women with distal radius fracture daily for 3 months following the fracture formation.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously demonstrated in many prospective studies that subcutaneous or intranasal application of SC exhibited analgesic effects . It was shown that calcitonin provided anti‐hyperalgesic effect on pain behaviours in chronic constriction injury‐induced hyperalgaesia in rats . In a clinical prospective study, 200 IU of intranasal SC was administered to postmenopausal women with distal radius fracture daily for 3 months following the fracture formation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that administration of elcatonin ameliorates enhanced arterial contractility 24) and repeated administration of elcatonin is attributable to normalization of the sodium channels expression in chronic constriction injury neuropathic rats. 25) Thus, restoration of the expression level of the sodium channels may be one of the mechanisms of the anti-allodynic effects of calcitonins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, calcitonin receptors have been reported to express in peripheral nerve tissues such as Schwann cells, not in dorsal root ganglion cells. 25) Therefore, we assume that neurotrophic factors derived from peripheral nerve tissues by stimulation of calcitonin receptors could modify the gene expression in dorsal root ganglion cells and regional blood flow. Further investigation is still required to determine the exact mechanisms by which calcitonins take effect, including modulation of these thermosensitive channels and Na + channels, and regional blood flow, through the activation of calcitonin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…10,11) Calcitonin also has the ability to relieve pain associated with a variety of disorders, including osteoporosis. [12][13][14][15][16] These actions are mediated by increased cAMP and intracellular Ca 2+ levels evoked by the stimulation of calcitonin receptors coupled to G proteins. [17][18][19] Cutaneous flushing is one of the most common side effects of calcitonin and the effects of elcatonin, a synthetic analog of eel calcitonin, 20) might be closely associated with plasma levels of vasoactive intestinal peptide.…”
mentioning
confidence: 99%